Vers une nouvelle conception des valeurs : apport de la psychologie à la criminologie des valeurs - Goyer-Michaud, Francyne; Debuyst, Christian (Acta Criminologica)

(untitled) (Les Presses de l'Université de Montréal, 1973)
AbstractTOWARD A NEW CONCEPT OF VALUES : PSYCHOLOGY'S CONTRIBUTION TO VALUE CONCEPTS IN CRIMINOLOGYThe present article introduces a new style of presentation to our review. It was not written by a team, but is the beginning of a dialogue between authors. Part Three by Christian Debuyst is a commentary on the first two sections written by Francyne Goyer-Michaud, which bear on values in psychology and on the elaboration of a new concept of values and its application to juvenile delinquency.Using the guiding theory developed by Spranger and Allport, in which values are defined as the motivations which predispose behaviour, a new concept of values is established — « motivational » values. There would be intermediary values between the individual and the world of values to which he adheres which induce both his values and his non-values, and which receive their power to do so from one of the well-known motivations — anxiety. It became possible, then, to attach to motivating values a typology based on anxiety. In this way, we infer that there are four types of motivating values resulting from anxiety : hedonistic anxiety where behaviour is guided by both the search for pleasure and escape from unpleasantness ; other-directed anxiety which is the fear of losing the love of one's peers ; authority-oriented anxiety, which is fear of the disapproval of authority figures ; and last, integral anxiety, where one fears a lowering of self-esteem. A study of the characteristics of young delinquents made it possible to establish the hypothesis that, in comparison with their socially integrated peers, they were more susceptible than the latter to the first two types of anxiety, and less susceptible to the other two.Along with the formulation of this new concept, the various methods used in measuring the values were studied to select the one that seemed the most suitable for the problem in question.Christian Debuyst bases his critical view of the study of values on four questions that came to mind after reading the text of Francyne Goyer-Michaud. The first concerns the concept of values itself. He believes a differentiation must be made between functional values and true values, and that the motivational values developed by Francyne Goyer-Michaud apply only to the first. He next reflects on anxiety as a source of values, advancing the theory that fear constitutes the motivation of a rather elementary morality which, though it never completely disappears, must eventually be replaced by a higher morality where others are seen as a value.After thinking about the concepts of personality which underly the type of adherence to values, he recognizes two presuppositions in the theory of the personality serving as the basis for the idea of values proposed by Francyne Goyer-Michaud : psychic economy leading to a reduction of tension, a completely Freudian concept, and a very sociological definition of the socialization process. What we have learned from the study of animal psychology, however, leads him to believe that everything cannot be explained by the search to reduce tension. We must therefore reach a theory of personality in which the attitude which an individual adopts towards a valued object is not dictated by the group nor by its sanction, but derives directly from the link that is established with the object he perceives to be a value.Finally, discussing the importance of this in its relation to criminology, he arrives at the three following conclusions : 1) the delinquent act cannot be looked upon as solely the breaking of a rule, but as the realization of a value — in this case the group, which is very demanding and requires submission. 2) Most of the time, delinquents show deficientattachment to values and that attachment is merely functional. 3) At the treatment level, in order to have delinquents adhere to true values, we must give them access to experiences that are significant and motivating.